2017
DOI: 10.1093/jxb/erx404
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MdCCD7 in the scion determines the extent of sylleptic branching and the primary shoot growth rate of apple trees

Abstract: This is the first case of wild-type roots being unable to suppress branching in a strigolactone-deficient scion. MdCCD7 RNAi primary shoots also exhibited an increased growth rate relative to the wild type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 70 publications
2
9
0
Order By: Relevance
“…SL research in wheat, specifically, is highly unexplored relative to rice and Arabidopsis . As there is evidence of species-specific variation in SL function which is linked to the developmentally regulated physical size of the organism of study ( Foster et al, 2017 ), future research should aim to elucidate the wheat-specific regulatory networks underlining SL’s role in abiotic stress.…”
Section: Advancements In Hormone-dependent Abiotic Stress Signalingmentioning
confidence: 99%
“…SL research in wheat, specifically, is highly unexplored relative to rice and Arabidopsis . As there is evidence of species-specific variation in SL function which is linked to the developmentally regulated physical size of the organism of study ( Foster et al, 2017 ), future research should aim to elucidate the wheat-specific regulatory networks underlining SL’s role in abiotic stress.…”
Section: Advancements In Hormone-dependent Abiotic Stress Signalingmentioning
confidence: 99%
“…In the bioenergy plant Jatropha curcas , SLs antagonistically regulate the axillary bud outgrowth in interactions with cytokinin and gibberellin [ 15 , 16 ]. Several recent reports have also demonstrated that manipulation of the expression of SL biosynthesis genes can lead to significant change of the shoot branching phenotype in Populus and Malus [ 17 , 18 ], indicating that SLs have significant functions on the morphogenesis of woody plants. Plant growth and seed yield of woody plants are also threatened by abiotic stresses, such as salt, drought, and cold.…”
Section: Introductionmentioning
confidence: 99%
“…The 10′-apo-β-carotenal is then cleaved by CCD8 to produce carlactone, which is a precursor of SLs [ 41 ]. CCD7 and CCD8 genes have been identified in the SLs synthetic pathways of several plant species, including Arabidopsis , pea, rice, tomato, saffron, Phelipanche aegyptiaca , maize, apple, poplar and petunia [ 19 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. The expression levels of SlCCD8 and SlCCD7 down-regulated by RNA interference reduced strigolactone concentrations in tomato [ 43 , 46 ].…”
Section: Introductionmentioning
confidence: 99%